1994
DOI: 10.1161/01.cir.90.4.1715
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in the management and long-term outcome of acute myocardial infarction. A statewide study. MIDAS Study Group. Myocardial Infarction Data Acquisition System.

Abstract: Women with acute myocardial infarction are less likely to have invasive cardiac procedures and have higher 3-year adjusted death rate up to age 70 than men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
93
3
1

Year Published

1997
1997
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 220 publications
(104 citation statements)
references
References 38 publications
7
93
3
1
Order By: Relevance
“…Previous studies have documented gender differences between men and women in procedure use and mortality among patients hospitalized with myocardial infarction, [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] but few studies have assessed whether there are differences in processes and outcomes that require patient perceptions to measure. We found that women had worse health status outcomes than men, as indicated by worse physical and mental health, a greater likelihood of spending time in bed due to ill health, and a lower likelihood of returning to work 3 months after discharge; however, we found no differences in the quality of interpersonal communication or health behavior counseling for men and women.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies have documented gender differences between men and women in procedure use and mortality among patients hospitalized with myocardial infarction, [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] but few studies have assessed whether there are differences in processes and outcomes that require patient perceptions to measure. We found that women had worse health status outcomes than men, as indicated by worse physical and mental health, a greater likelihood of spending time in bed due to ill health, and a lower likelihood of returning to work 3 months after discharge; however, we found no differences in the quality of interpersonal communication or health behavior counseling for men and women.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] Women hospitalized with myocardial infarctions are less likely to be treated with thrombolytics or revascularization. [1][2][3][4][5][6] Women also have a higher mortality rate following myocardial infarction, which may be partially explained by higher ages and increased comorbidity.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…1 Despite this increased risk of mortality, studies have continually showed delayed treatment in women with coronary artery disease (CAD), particularly with invasive procedures such as diagnostic catheterization. [2][3][4][5][6][7][8][9] Women are also less likely to receive front-line intervention such as electrocardiogram (ECG), oxygen saturation measurement, and evidence-based pharmacotherapies. [10][11][12] Research has identified a number of explanations for these discrepancies, which can be categorized into three general themes: quantifiable clinical differences, physician bias, and patient preferences.…”
Section: Introductionmentioning
confidence: 99%